Building Vocabulary Knowledge in Preschoolers Through Shared Book Reading and Gameplay. Issue 2 (25th May 2016) - Hassinger‐Das, Brenna; Ridge, Katherine; Parker, Amira; Golinkoff, Roberta Michnick; Hirsh‐Pasek, Kathy; Dickinson, David K.
ABSTRACT: This study moves beyond previous investigations to examine whether an educational intervention combining shared book reading with a vocabulary game increases children's vocabulary knowledge. Four‐year‐olds ( N = 44) were randomly assigned to dyads in either an intervention (shared book reading plus vocabulary review game) or comparison condition (shared book reading, after‐reading vocabulary review, and game that did not teach vocabulary). After two 30‐min sessions, results demonstrated that the intervention condition outperformed the comparison condition on measures of receptive and expressive knowledge of taught vocabulary words. Children in the intervention group who scored the lowest at pretest on the receptive measure saw the most gains in taught word knowledge. Findings suggest that combining vocabulary gameplay with shared book reading improved children's learning of the vocabulary words in comparison to a comparison group.